The Development of a Sub-Surface Monitoring System for Organic Contamination in Soils and Groundwater. (2002) - Huntley, Sharon L.; Ritchie, Lawrence J.; Setford, Steven J.; Saini, Selwayan
Abstract : A major problem when dealing with environmental contamination is the early detection and subsequent surveillance of the contamination. This paper describes the potential of sub-surface sensor technology for the early detection of organic contaminants in contaminated soils, sediments, and landfill sites. Rugged, low-power hydrocarbon sensors have been developed, along with a data-logging system, for the early detection of phase hydrocarbons in soil. Through laboratory-based evaluation, the ability of this system to monitor organic contamination in water-based systems is being evaluated. When used in conjunction with specific immunoassays, this can provide a sensitive and low-cost solution for long-term monitoring and analysis, applicable to a wide range of field applications.